A Study on The Influence of Country of Origin and Perceived Quality on The Purchase Intention For Pre-Owned Electric Vehicles of Chinese Brands in Jabodetabek - Aditya Yuli indrawan; Fairuz Rizky Utami; Woro Endah Waraswati; Faranita Mustikasari (Eduvest - Journal of Universal Studies, 2026)
This study explores the factors influencing the purchase intention of used electric vehicles (EVs) from Chinese brands in the Greater Jakarta area. The research focuses on the roles of Country of Origin (COO) and perceived quality in shaping consumer behavior. As the global transition toward sustainable transportation accelerates, electric vehicles have gained prominence; however, the used EV market—particularly for Chinese brands—remains underdeveloped in Indonesia. A quantitative approach using Structural Equation Modeling (SEM) was employed to analyze data collected from 150 respondents in the Greater Jakarta area. The findings indicate that COO significantly influences consumers’ perceptions of product quality and, consequently, their purchase intentions. Perceived quality serves as a critical mediating variable between COO and purchase intention. The study further reveals that perceived risk negatively affects purchase decisions, reflecting consumer concerns regarding product reliability and after-sales service. These findings enhance the understanding of consumer behavior in Indonesia’s emerging used EV market and offer practical implications for automotive businesses and policymakers. Specifically, the results suggest the need for strategies that strengthen brand credibility, improve perceived quality, and build consumer trust to encourage the adoption of electric vehicles, particularly within the secondary market.